GENEALOGY OF WASAṬIYYA WITHIN INDONESIAN SOCIETY: The Influence of Sufism in Indonesian Archipelago - Musa Alkadzim; Naura Safira Salsabila Zain; Muhammad Ulil Abshor (IAIN Ponorogo, 2023)
This article examines the genealogy of wasaṭiyya Islam in Indonesia. Historical processes of Islamization in the pre-Indonesia context have influenced how the Muslim majority of Indonesia demonstrates its moderate expression from historical periods to contemporary situations. The establishment of the Indonesian state has the heredity derivation from the past Islamization. The role of Sufism in the processes of Islamization is addressed here. Ash’arism or Aswaja paved the theological way for wasaṭiyya by choosing a position of moderation between rationalist and conservative extremist schools of thought. On a deeper level, this article concludes that the Sufi foundations of the early Islamization period are essential for establishing wasaṭiyya in Indonesia. When Pancasila, as the nation-state philosophy, incorporates cultural elements acknowledged by Muslim Ulama, it is evident that any attempt to undermine or pervert wasaṭiyya Islam in Indonesia will finally fail. This research applied qualitative methodology with an exploratory research design. The data were collected using literature studies from books, journals, and related articles.